Studi Tinjauan Pustaka: Faktor Risiko Kejadian Amputasi pada Pasien Kaki Diabetes Mellitus - Amalina, Nida; Djuwita, Ratna; Yunir, Em (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Diabetes mellitus increased from 6.9% in 2013 to 8.5% in 2018. This figure shows that only about 25% of people with diabetes know that they have diabetes. According to the International Working Group on the Diabetic Foot (IWGDF), 1 in 4 people with DM will develop an ulcer on their foot during their lifetime with a proportion of 19-34% of the total DM patients. Wound healing of DM ulcers often requires longer time and considerable resources and has a 40% risk of re-formation at 1 year and increases to 60% after 3 years.Methods: Articles selected based on the inclusion criteria were journals that examined the relationship between diabetic foot and amputation, either using a longitudinal design, cohort study (retrospective or prospective) or case control. The exclusion criteria were journals that were systematic literature reviews, screening, diagnosis.Results: Obesity in 2 articles mentioned that OR=1.20-3.20 had a significant association with amputation while blood glucose factor in 2 articles mentioned that OR=2.92-9.43 had a statistically significant association with amputation. It was found in these 3 articles with OR range=6.9-13.97, poorly controlled HbA1c had a statistically significant association with amputation.Conclusion: This literature review study concluded that amputation risk factors are influenced by BMI and blood sugar levels. Patients should be educated on the importance of maintaining good blood sugar control, in addition to wearing proper footwear, avoiding repetitive mechanical trauma to the foot, and performing regular foot examinations.